Adrenal Crisis – Definition, Prevention and Treatment: Results from a Delphi Survey - Kienitz, Tina; Bechmann, Nicole; Deutschbein, Timo; Hahner, Stefanie; Honegger, Jürgen; Kroiss, Matthias; Quinkler, Marcus; Rayes, Nada; Reisch, Nicole; Willenberg, Holger Sven; Meyer, Gesine (Hormone and Metabolic Research, 2023)
Based on recent data, a total number of about 29 000 patients with adrenal insufficiency can be calculated for Germany, and about 1500 fatalities due to adrenal crises have to be expected within the next decade. Management of adrenal crises is still unsatisfactory. The objectives of this study were to establish consensus for diagnostic criteria, prevention strategies, and treatment recommendations for adrenal crises. The study was conducted from January 2022 to April 2023, using Delphi technique. Four rounds of questionnaires were sent to 45 experts, selected by a coordinating group on behalf of the adrenal section of the German Society of Endocrinology. The survey was implemented online using the REDCap web application. Responses were captured anonymously. During the Delphi process the expert panel developed diagnostic criteria to identify patients likely to have an adrenal crisis. Education about adrenal insufficiency among patients as well as non-endocrine medical personnel were regarded as highly important. It was suggested that recommendations for the management of adrenal insufficiency have to be simplified and made widely available. This study provides pragmatic strategies to identify and treat patients prone to adrenal crisis, thereby highlighting the need for an improved management of patients with adrenal insufficiency.
Keywords: adrenal insufficiency; glucocorticoid replacement; adrenal crisis; emergency card; diagnostic criteria